Construction and validity of the Interprofessional Communication in Health Scale - Cláudia Patrícia da Costa Brás; Manuela Maria Conceição Ferreira; Maria do Céu Aguiar Barbieri de Figueiredo (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to construct and validate the Interprofessional Communication Scale in Health. Methods: a psychometric study was carried out on a sample of 360 nurses from a hospital and university center in central Portugal. Reliability was assessed through internal consistency and construct validity through exploratory and confirmatory factor analysis. Results: the Interprofessional Communication in Health Scale, consisting of 27 items, is organized into 3 factors: "Teamwork", "Conflict management" and "Leadership", with a total variance of 51.1%. Good internal consistency was obtained, with a Cronbach's alpha of 0.842, and adequate Goodness of Fit Index model. Conclusions: the Interprofessional Communication in Health Scale presents a factorial structure with adequate validity and reliability results, and may constitute a useful self-report instrument in assessing interprofessional communication in health.